Challenges of international retirees in second home destination: A phenomenological analysis - Wong, K.M.; Musa, G. (Elsevier, 2015)
The increase in aging population globally stimulates the demand for international retirement travel. Even though unsatisfactory retirement experiences could deter its growth potential, little knowledge is available on the retirees' challenges encountered at the second home destination. The study responds to the discouraging growth of European retirees in Malaysia, compared with Asian counterparts. Being "problem based" in nature, this study employed in-depth phenomenological method. Twenty-three international retirees in Malaysia were interviewed, and the data were analyzed using NVivo. We also triangulated the data with several primary and secondary sources. The paper highlights new perspectives on the challenges related to unclear rules and regulations, unprofessional officers, unreliable postal service, and unstandardized banking procedures, which deserve certain attention from the second home destination promoters. The findings provide useful pointers for professional practitioners in product development and marketing of international second home destination.